Challenging the understanding of significant improvement and outcome in schizophrenia – the concept of reliable and clinically significant change methods. Issue 1 (14th July 2015) - Schennach, Rebecca; Möller, Hans‐Jürgen; Obermeier, Michael; Seemüller, Florian; Jäger, Markus; Schmauss, Max; Laux, Gerd; Pfeiffer, Herbert; Naber, Dieter; Schmidt, Lutz G.; Gaebel, Wolfgang; Klosterkötter, Joachim; et al.
Abstract: Significant changes of schizophrenia patients during inpatient treatment were evalutaed and compared to established outcome criteria. The concept of reliable and clinically significant change methods was applied to three hundred and ninety‐six patients suffering from a schizophrenia spectrum disorder. First, information on whether or not the change of the patient's condition is sufficient in order to declare that it is beyond a measurement error or random effect (= reliable change) was evaluated and in a second step it was observed if the reliable change was clinically meaningful (= clinically significant change). Different Positive and Negative Syndrome Scale for Schizophrenia (PANSS) thresholds were applied to define the clinically significant change (40, 45 and 50 points). These changes were then compared to established outcome criteria such as response and remission. Seventy‐nine of the 396 patients (20%) showed a reliable improvement of symptoms, whereas 70% improved without achieving a reliable change of their condition. Of the 79 patients achieving a reliable change during treatment 8‐15% concurrently showed a clinically significant change depending on the respective PANSS threshold. In contrast, 56% of the patients achieved response and 60% were in remission at discharge when applying established outcome criteria. Our results showed that a rather small number of schizophrenia patients were found to reliably change during inpatient treatment, with even less patients achieving a clinically significant change. The concept of reliable and clinically significant changes revealed to be a lot more stringent than today's established outcome criteria and should be critically evaluated regarding its use in schizophrenia patients. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Significant changes of schizophrenia patients during inpatient treatment were evalutaed and compared to established outcome criteria. The concept of reliable and clinically significant change methods was applied to three hundred and ninety‐six patients suffering from a schizophrenia spectrum disorder. First, information on whether or not the change of the patient's condition is sufficient in order to declare that it is beyond a measurement error or random effect (= reliable change) was evaluated and in a second step it was observed if the reliable change was clinically meaningful (= clinically significant change). Different Positive and Negative Syndrome Scale for Schizophrenia (PANSS) thresholds were applied to define the clinically significant change (40, 45 and 50 points). These changes were then compared to established outcome criteria such as response and remission. Seventy‐nine of the 396 patients (20%) showed a reliable improvement of symptoms, whereas 70% improved without achieving a reliable change of their condition. Of the 79 patients achieving a reliable change during treatment 8‐15% concurrently showed a clinically significant change depending on the respective PANSS threshold. In contrast, 56% of the patients achieved response and 60% were in remission at discharge when applying established outcome criteria. Our results showed that a rather small number of schizophrenia patients were found to reliably change during inpatient treatment, with even less patients achieving a clinically significant change. The concept of reliable and clinically significant changes revealed to be a lot more stringent than today's established outcome criteria and should be critically evaluated regarding its use in schizophrenia patients.